KINETIKA DEGRADASI SELULOSA ASETAT DARI SABUT PINANG - Intan Syahbanu; Annisa Anugraini; Husna Amalya Melati (Indonesian Journal of Pure and Applied Chemistry, 2018)
Cellulose Acetate is a material with wide range in applications. Cellulose acetate may obtain from natural resources, such as areca fiber. Polymers should have uniform molecular weight for the applications and could be modify by ultrasonic waves. Ultrasonic treatment on polymer entangled with polymer degradation. In this research, degradation kinetics of cellulose acetate in acetone had been studied. Analysis was performed by determination of intrinsic viscosity in polymer solution system.  Intrinsic viscosity was successfully obtained by fitting data using Huggins equation, indicate molecular interaction in polymer solution should not be neglected.  Increasing in sonication time reducing the intrinsic viscosities as well as molecular size in solutions.  Degradation rate constant and reaction order were obtained 5,975x10-3(g.mL-1)0,1.min-1 and 1,0616, respectively.  Kinetics model was successful to determine the degradation rates of cellulose acetate on acetone by correlation coefficient (R2) at 0,966.